Tenancy Relations in India: Observations from a field study - S. Mohanakumar (Institute of Development Studies, 2014)
Approaches of different schools of thought to tenancy have been different for its impact on agriculture. As agriculture and allied activities have increasingly become loss making venture for more than last two decades. Farmers, especially the food crop producers, have either shifted to more profitable commercial crops or lease out land to farm workers and peasants for rent. Wage labour and peasants are rather forced to lease-in land to make up for the loss in employment days in the crop production sector. It is argued that forced tenancy of wage labour and peasants is a variant of hunger leasing and such tenants are subjected to multiple forms of exploitation by money lenders, land owners, and traders of agricultural commodities. The price fall of agricultural commodities driven agrarian distress and its culmination into massive spate of suicides is closely linked to the lease land cultivation by peasants, wage labour and small farmers.